Inhibition of a Novel CLK1-THRAP3-PPARγ Axis Improves Insulin Sensitivity - Wang, Zhenguo; Gao, Xiaojing; Li, Qingrun; Zhu, Hongwen; Zhao, Xiangjie; Garcia-Barrio, Minerva; Zhang, Jifeng; Guo, Yanhong; Chen, Y. Eugene; Zeng, Rong; Wu, Jia-Rui; Chang, Lin (Frontiers in Physiology, 2021)
Increasing energy expenditure by promoting “browning” in adipose tissues is a promising strategy to prevent obesity and associated diabetes. To uncover potential targets of cold exposure, which induces energy expenditure, we performed phosphoproteomics profiling in brown adipose tissue of mice housed in mild cold environment at 16°C. We identified CDC2-like kinase 1 (CLK1) as one of the kinases that were significantly downregulated by mild cold exposure. In addition, genetic knockout of CLK1 or chemical inhibition in mice ameliorated diet-induced obesity and insulin resistance at 22°C. Through proteomics, we uncovered thyroid hormone receptor-associated protein 3 (THRAP3) as an interacting partner of CLK1, further confirmed by co-immunoprecipitation assays. We further demonstrated that CLK1 phosphorylates THRAP3 at Ser243, which is required for its regulatory interaction with phosphorylated peroxisome proliferator-activated receptor gamma (PPARγ), resulting in impaired adipose tissue browning and insulin sensitivity. These data suggest that CLK1 plays a critical role in controlling energy expenditure through the CLK1-THRAP3-PPARγ axis.